Diversity, Structural, and Regeneration Analysis of Woody Species in the Afromontane Dry Forest of Harego, Northeastern Ethiopia - Belachew Bogale Worku; Emiru Birhane Hizkias; Seid Muhie Dawud (International Journal of Forestry Research)
The study was conducted in the Harego dry Afromontane forest, Northeastern Ethiopia, to analyze woody species composition, diversity, structure, and regeneration status. To collect the vegetation data, a total of 67 sample plots measuring 400m220m×20m were laid systematically. Species identity, abundance, height, and diameter at breast height (DBH) were recorded for each sample plot. Diversity, structural, and regeneration status were analyzed for the forest. A total of 50 woody species representing 35 families and 44 genera were identified and recorded. According to the IUCN Red List Category, Rhus glutinosa A. Rich and Prunus africana (Hook.f.) Kalkm. are vulnerable species. Fabaceae was the dominant family, and of the total species, 27 were shrubs, 19 were trees, and 4 were climbers. The species accumulation curve indicates that the majority of plant species in the study area were captured by our sampling efforts. The values of true Shannon (N1 = 17) and true Simpson (N2 = 11) indicate that species in the Harego forest are more or less evenly distributed. The abundance-frequency ratio of all woody species (WI = >0.05) indicates the heterogeneity of species composition. The total density and basal area were 4400 stems ha−1 and 9.66 m2 ha−1, respectively. The majority of the species fallen into the lower IVI classes. The diameter and height class distribution revealed an inverted J-shape. The increase in population demand and disturbance shows a high variation in stand structure and hampered natural regeneration, which needs immediate conservation actions.